2004
DOI: 10.1086/422534
|View full text |Cite
|
Sign up to set email alerts
|

Association ofIL12RB1Polymorphisms with Pulmonary Tuberculosis in Adults in Morocco

Abstract: Five disease-causing genes, including the IL12RB1 gene that encodes the beta 1 chain of the receptor for interleukin (IL)-12 (IL-12R beta 1), are known to be associated with the syndrome of Mendelian susceptibility to mycobacterial diseases. Some IL-12R beta 1-deficient patients present with tuberculosis as the only clinical phenotype. A comprehensive genetic study of IL12RB1 was conducted among 101 Moroccan families, including 157 offspring (age, >15 years) who had culture-positive pulmonary tuberculosis (PTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 26 publications
1
44
3
Order By: Relevance
“…These combined immunological defects leave IL12RB1 mut individuals more susceptible to infection by mycobacteria, Salmonella, and Candida species, as reported in a recent extensive international study (20). Smaller and more regional studies have also shown positive associations between IL12RB1 deficiencies (13,14,21,23,(51)(52)(53) or IL12RB1 polymorphisms (16,22,(54)(55)(56)(57) and susceptibility to a number of other maladies and infectious diseases. However, notably, beneficial IL12RB1 polymorphisms also have been discovered (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…These combined immunological defects leave IL12RB1 mut individuals more susceptible to infection by mycobacteria, Salmonella, and Candida species, as reported in a recent extensive international study (20). Smaller and more regional studies have also shown positive associations between IL12RB1 deficiencies (13,14,21,23,(51)(52)(53) or IL12RB1 polymorphisms (16,22,(54)(55)(56)(57) and susceptibility to a number of other maladies and infectious diseases. However, notably, beneficial IL12RB1 polymorphisms also have been discovered (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…An IL-12B 3=-UTR SNP (rs3212227) was identified as a risk factor for pulmonary TB in populations of African origin in a confirmation study (152). Polymorphisms in the IL-12 receptor gene, IL-12RB1, have also been implicated in the development of TB in Moroccan (181) and Japanese (113) populations but not in Koreans (116).…”
Section: Il-12mentioning
confidence: 99%
“…They reported no significant association between alleles or genotypes and susceptibility to Prabhu Anand et al (24) and Ma et al (25) found that allelic as well as genotypic frequencies of IL-12B 1188 A/C (rs3212227) did not differ significantly between the patients and normal subjects. Lee et al (12) in a study on Korean population found no significant association between PTB and the IL-12R polymorphism while, Remus et al (13) showed a positive correlation between IL-12R polymorphism and susceptibility to TB and pointed out that the polymorphism in IL12-R may affect the risk of PTB development. Interleukine-12 influence on macrophage to controlling MTB (26) and polymorphism in IL-12 and its receptors may affect its production.…”
Section: Reverse Outer Agctcctctcactggtcccctt Forward Inner (A Allelementioning
confidence: 98%
“…Reduced expression of IL12Rβ can cause immunodeficiency of MTB patients (9). Several studies have shown the association among IL-12A, IL12-B and its receptor polymorphism with the risk of TB but the results were controversial (10)(11)(12)(13). Therefore, the present case-control study was designed to investigate the possible association between IL12A rs568408, IL12B rs3212227 and IL-12R rs383483 polymorphisms and PTB in a sample of southeast Iranian population.…”
Section: Introductionmentioning
confidence: 95%